2017
DOI: 10.1002/cne.24282
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the transcriptome during the estrous cycle in four regions of the mouse brain

Abstract: We analyzed the transcriptome of the C57BL/6J mouse hypothalamus, hippocampus, neocortex, and cerebellum to determine estrous cycle-specific changes in these four brain regions. We found almost 16,000 genes are present in one or more of the brain areas but only 210 genes, ∼1.3%, are significantly changed as a result of the estrous cycle. The hippocampus has the largest number of differentially expressed genes (DEGs) (82), followed by the neocortex (76), hypothalamus (63), and cerebellum (26). Most of these DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 162 publications
(210 reference statements)
6
24
1
Order By: Relevance
“…The analysis showed that changes in gene expression in the cerebral cortex mediated by the LCKD are relatively small when compared with those in the liver. Obvious changes (log 2 ratio < −4, P < 0.01) were observed only for the genes Prl and Gh (Table 2), which encode the pituitary hormones prolactin and growth hormone, respectively, and are known to be expressed in the cerebral cortex 34,35 . Several studies have reported a relationship between the expression of these genes and epilepsy 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that changes in gene expression in the cerebral cortex mediated by the LCKD are relatively small when compared with those in the liver. Obvious changes (log 2 ratio < −4, P < 0.01) were observed only for the genes Prl and Gh (Table 2), which encode the pituitary hormones prolactin and growth hormone, respectively, and are known to be expressed in the cerebral cortex 34,35 . Several studies have reported a relationship between the expression of these genes and epilepsy 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…During the estrous cycle expression of a small number of genes in the hippocampus of the female mouse changes significantly (DiCarlo, Vied, & Nowakowski, ; Spencer, Waters, Milner, & McEwen, ). To ensure that the estrous cycle did not confound comparisons of interest, the estrous stage was determined for sexually mature females (2 and 4 months of age) at the time of tissue collection.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to what happens in other brain areas, the hippocampus is a site of extrapituitary GH expression [ 120 , 121 ], which also leads to the notion that autocrine and/or paracrine regulatory mechanisms are involved in these actions. Interestingly, it was shown that GH expression in the amygdala, a functional related structure contiguous to the hippocampus, increased under chronic fear and during fear learning conditions [ 122 ].…”
Section: Expression and Neurotrophic Effects Of Growth Hormone (Ghmentioning
confidence: 99%